What are the specific disability and limitation types underlying responses to the BRFSS disability questions?. Issue 1 (January 2015) - Mann, Joshua; Balte, Pallavi; Clarkson, John; Nitcheva, Daniela; Graham, Catherine Leigh; McDermott, Suzanne
Abstract: Background: Researchers rely on resources such as BRFSS data to understand the health status of people with disability. However, the survey data rely on a limited definition of disability resulting in imprecise inferences about the nature of disability. Understanding how health varies among people with different types of disability is vital to tailoring interventions for improving health and eliminating disparities. Objective: The purpose of this study was to utilize state added follow-up questions in the 2011 South Carolina BRFSS to describe the specific health conditions and limitations attributed to their disability and to compare health status across different types of disability. Methods: Participants reporting a disability were asked to name health condition(s) causing disability and describe their disability-related limitations. Descriptive statistics were calculated using weighted proportions. Logistic regression was used to model the associations of specific health conditions and limitations with the outcomes of self-rated general health and mental health status, controlling for demographic factors. Results: The 5 most commonly reported health condition categories were (weighted percentage): musculoskeletal (68.56%); pulmonary (10.41%); neurologic (8.48%); heart disease (8%) and mental health (7.31%). The 5 most commonly reported limitation categories were: mobility/balance limitations (46.29%); pain (23.22%); breathing problems (12.36%); general weakness/fatigue (9.57%) and limited lifting (8.24%). There was substantial variation in the degree of association between categories of conditions and limitations and the outcomes of self-rated physical and mental health. Conclusions: Researchers and practitioners should consider variability in the nature of disability when designing interventions to improve the health of people with a disability.